Expression of Platelet Membrane Glycoprotein V in Human Megakaryocytes and Megakaryocytic Cell Lines: A Study Using a Novel Monoclonal Antibody against GPV - Takafuta, Toshiro; Fujirmura, Kingo; Kawano, Hironori; Noda, Masaaki; Fujimoto, Tetsuro; Oda, Kenji; Shimomura, Takeshi; Kuramoto, Atsushi (Thrombosis and Haemostasis, 1994)
Glycoprotein V (GPV) is a platelet membrane protein with a molecular weight of 82 kD, and one of the leucine rich glycoproteins (LRG). By reverse transcription-polymerase chain reaction (RT-PCR), GPV cDNA was amplified from mRNA of platelets and megakaryocytic cell lines. However, since there are few reports indicating whether GPV protein is expressed in megakaryocytes as a lineage and maturation specific protein, we studied the GPV expression at the protein level by using a novel monoclonal antibody (1D9) recognizing GPV. Flow cytometric and immunohistochemical analysis indicated that GPV was detected on the surface and in the cytoplasm of only the megakaryocytes in bone marrow aspirates. In a megakaryocytic cell line UT-7, GPV antigen increased after treatment with phorbol-12-myri-state-13-acetate (PMA). These data indicate that only megakaryocytes specifically express the GPV protein among hematopoietic cells and that the expression of GPV increases with differentiation of the megakaryocyte as GPIb-IX complex.